PERKAWINAN HUKUM ADAT SUKU ANAK DALAM DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI DESA SANGLAP KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Candra. H, Limboy Alex; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Tribe Anak Dalam (SAD) or often also called the Kubu Tribe, is a group of peoplewho live in the jungle of the jungle with the pattern of moving (Nomad), Tribe Anak Dalam /Orang Rimba have their own custom law or tradition that has been inherent in them which istheir life reference or guide. in the Tribe Children In husbands can marry the youngersiblings of his wife as long as the husband is still able to support the birth and the inner wifeor also called the relationship semenda. From the background, the authors conducted a studytitled "Marriage of Children Tribe Reviewed From Law Number 1 Year 1974 AboutMarriage in Sanglap Village District Batang Cenaku Indragiri Hulu".The problems that the author made the basis in this study is how the process ofmarriage in the village of children in the village of Sanglap Batang Cenaku district IndragiriHulu district viewed from the law number 1 year 1974 about marriage and the factorscausing the occurrence of marriage semenda on tribe children. While the purpose of writing,among others, to know the process of marriage in the tribe of children in green from lawnumber 1 year 1974 about marriage and to know the factors causing the occurrence ofmarriage semenda on the tribe of children in this type of research can be classified in thetype of sociological or empirical legal research, because in this study the authors directlyconduct research on the location or place studied in order to provide a complete and clearpicture of the problem under study. This research was conducted in Sanglap village, BatangCenaku sub-district, Indragiri Hulu district. Source used, namely: primary data andsecondary data. Data collection techniques in this study with observation, interviews, andliterature review.The results obtained from this study are first, customary law of Tribe Anak Dalamallows married husband more than one or commonly called polygamy, and they usually havepolygamy with younger siblings who mean they have a relationship semenda. The tribe ofchildren in no belief or atheist, they only trust the gods and spirits of their ancestors otherthan that the tribe of children do not understand about the rules that apply because theeducational background, almost entirely in the Tribe Anak Dalam did not get education.Marriage in the Children's Tribe In contrast to Law No. 1 of 1974 concerning marriage.Tribe Anak Dalam usually married under the age and didalm Marriage Act is prohibitedprecisely in chapter 7 on the marriage age limit, and article 8 about the marriage of twopeople because it has a relationship semenda. The Inner Child Tribe lineage is patrialalbecause the inner child tribe.Keywords: Inner Tribe, Marriage Semenda, Customary Law